The effect of hypoxia on nitric oxide and endothelial nitric oxide synthase in the whole heart and isolated cardiac cells: the role of the PI3–K / PKB pathway as a possible mediator. - Chamane, Nontuthuko Zoleka Lynette (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScMedSc (Biomedical Sciences. Medical Physiology))--University of Stellenbosch, 2009.